Hacia una reformulación de la comunidad internacional y el futuro del Derecho comunitario - Hakansson Nieto, Carlos (Revista de Derecho, 2019)
The success of the European Union is the paradigm which should be taken into account by the other integration blocks or movements (NAFTA, Andean Community, Caricom, African Union, APEC, etc) with the aim of not only jointly forming, thanks to the start of relations, a global commercial space but also the future reformulation of an international community which, just like the European Union; could generate its own institutions that in time could even substitute the United Nations Organization and start dreaming about other forms of organizations.